Peranan Marketing Mix Terhadap Keputusan Konsumen Memilih Keluncum Barbershop Sepinggan Balikpapan - Rudy Pudjut Harianto; Surya Adi Wibowo (Jurnal MEBIS (Manajemen dan Bisnis), 2017)
Abstract : This research aims to analyze the effect of marketing mix toward decision consumers to choose Barbershop Keluncum at Balikpapan. Types of research method is combined/mixed, using qualitative and quantitative methods (mixed methods). Data Analyse method that used in this research are Multiple Linier Regression Analyse (correlation coeficient, determination coeficient, and t test/significantion test). Accumulatively, coeficient correlation (R) = 0,764 so that it can be said that the independent variables toward dependent variable in this research can giving the strength correlation. Result of determination coefficient (R2) = 0,578 it can be said the independent variables can be explain the dependent variable of equal to 57,8% only. While the rest equal to 42,2% explained by other variable from outside model. The result of significantion test could be explained : there are have a positive significant effect to influence of decision consumers .